The Effect of Instrumental Music on Concentration and Interpersonal Intelligence Among First-Grade Students - Riana, Vina; Wong, Mettadewi; Bramantyo, Hastho (Jurnal Mamangan, 2024)
This research aims to explore and analyze the influence of instrumental music on the concentration and intrapersonal intelligence of 1st-grade students at SD Dhammāsoka Banjarmasin in the 2024/2025 academic year, second semester. The selection of SD Dhammāsoka as the research location was based on a gap in previous research that had not specifically delved into the influence of instrumental music on these two aspects in 1st-grade elementary students using a qualitative approach and Classroom Action Research (CAR) method within this school context. The challenges of learning concentration and the development of intrapersonal intelligence in early childhood students are crucial issues that require innovative interventions, and instrumental music is believed to have the potential to create a conducive learning atmosphere and facilitate self-reflection. The research questions include: (1) How does the use of instrumental music affect the concentration of 1st-grade students at SD Dhammāsoka? (2) How can the implementation of instrumental music improve the intrapersonal intelligence of 1st-grade students at SD Dhammāsoka? (3) How effective is the application of Classroom Action Research (CAR) in optimizing learning with instrumental music at SD Dhammāsoka? This research used the Classroom Action Research (CAR) method, conducted in three cycles. Each cycle consists of four stages: planning, action implementation, observation, and reflection. The research subjects were 18 1st-grade students of SD Dhammāsoka and the class teacher as a participant. Data collection was carried out through observation (concentration and intrapersonal intelligence observation sheets), semi-structured interviews with teachers, students, and parents, and student reflective journals. The data were analyzed qualitatively using the Miles & Huberman method (data reduction, data display, conclusion drawing) and thematic analysis (Braun & Clarke, 2006), as well as quantitatively through a comparison of pretest and posttest results for concentration and intrapersonal intelligence. The research results show that the use of instrumental music significantly increased student concentration, as seen from the increase in the average concentration score from 3.5 (pretest) to 6.8 (posttest). In addition, students' intrapersonal intelligence also experienced a substantial increase, with an average score from 5.2 (pretest) to 9.5 (posttest), demonstrated by students' ability to identify and express feelings, and manage emotions. The application of CAR proved to be very effective in optimizing learning with instrumental music, allowing for continuous improvement and adaptation of strategies based on empirical findings in each cycle. The conclusion of this research is that instrumental music has a positive and significant influence on the improvement of concentration and intrapersonal intelligence of 1st-grade students at SD Dhammāsoka, and CAR is an effective method for implementing this intervention.